Development Of Religious CharacterEarly Childhood Trough The Historical Of Surah An-Nas - Syarifuddin, Zulfaidah Saputri (ACIECE, 2018)
The character of a child will determine the mindset, attitude, behavior that will become a personality.To form the ideal character, character education is needed in various types and levels of education,especially in early childhood, which is the placement of the first pillar of education. Religiouscharacters are the main of several characters that have been determined by the Ministry ofEducation. The development of religious character does not only contain a set of values which areonly limited to the cognitive, but should the values of the religion be known, loved so that they canbe realized in an action of lifetime, the value in question is Islam . Alquran as a complex muslim holybook has history in each of the suras and the verses are in the form of stories as a background. Thestory contained in Alquran is ideal to be imitated and interpreted in daily life, as in the history of theSurah An-nas has contained in it the values of religious character